Development of SUKA MAJU application using Google Workspace for academic supervision effectiveness - Hurriyati, Hurriyati; Syahril, Syahril; Gistituati, Nurhizrah; Irsyad, Irsyad (Indonesian Research Journal in Education |IRJE|, 2026)
This study addresses the continued reliance on manual academic supervision, with paper-based instruments still widely used despite rapid educational digitalisation and the integration of teacher performance assessment through the Merdeka Mengajar Platform (PMM). This condition creates challenges for school principals in understanding the supervision priorities and indicators aligned with PMM-based education report cards, leading to inconsistencies in academic oversight and hindering the effective implementation of educational strategies. This research aims to develop the SUKA MAJU application using Google Workspace for Education to support more effective and integrated academic supervision. The study employs a research-and-development approach based on the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation, practicality testing, and effectiveness evaluation involving school principals. The results indicate high validity (90%), strong practicality (82%), and high effectiveness (84%). These findings demonstrate that the SUKA MAJU application effectively enhances the implementation of academic supervision in schools, leading to improved educational outcomes and better support for teachers' professional development.